HISTORICAL EMOTION IN MOVIES AND THE MOOD IN DELIVERY OF THE OPERATOR ROLE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
In this article, the names of several young filmmakers of the new independence period of Uzbek cinema are discovered. Their free and authorial creativity has contributed to the development of Uzbek cinema as a unique contribution. Each creator is given examples of his creative works, the cinematographer first of all builds the visual solution of the film in accordance with the dramaturgy and the image of the actors, and then the technical aspects of image quality are mentioned. Looking at the current situation of the creativity of Uzbek youth, suggestions and comments are made regarding the elimination of existing problems in creative cooperation.